Effects of Combat Sports on Cognitive Function in Older People: A Systematic Review - Herrera-Valenzuela, T (Edizioni Minerva Medica, 2024)
iNTroducTioN: This systematic review aimed to analyze the available body of published peer-reviewed studies on the effects of combat sports compared with active/passive control on cognitive function and electrophysiological markers of brain activity in older people. eVideNce acQuiSiTioN: The studies were searched in Scopus, Web of Science, pubMed, MedliNe, and psyciNfo databases from deadline to June 2023. The priSMa, TeSTeX, roB, and Grade scales assessed the evidence’s methodological quality and certainty of evidence. The protocol was registered in proSpero (code: crd42022361695). EVIDENCE SYNTHESIS: After reviewing 3768 studies, seven combat sports interventions (score ≥60% in methodological quality) were selected, composed of 381 older people (63% female), with a mean age of 66 years. In the selected studies, interventions based on judo, karate, and taekwondo were carried out, where it was not possible to verify the benefits of combat sports in cognitive function and electrophysiological markers of brain activity regarding active/passive control groups, although the individual results of the analyzed studies indicate that the practice of combat sports favor selective attention, divided attention, executive function, visual perception, and cognitive processing speed in older people. CONCLUSIONS: The available evidence does not allow a definite recommendation regarding combat sports as an effective cognitive function intervention in older people. (Cite this article as: ramos-espinoza f, Muñoz-Vasquez c, hernández-Martínez J, lucero B, herrera-Valenzuela T, Magnani Branco Bh, et al. effects of combat sports on cognitive function in older people: a systematic review. J Sports Med phys fitness 2024;64:301-10. doi: 10.23736/ S0022-4707.23.15578-2) © 2023 ediZioNi MiNerVa Medica.